Globalization, demand of sense and enemization of the other: A psychocultural analysis of European societies' sociopolitical crisis. (September 2019) - Salvatore, Sergio; Mannarini, Terri; Avdi, Evrinomi; Battaglia, Fiorella; Cremaschi, Marco; Fini, Viviana; Forges Davanzati, Guglielmo; Kadianaki, Irini; Krasteva, Anna; Kullasepp, Katrin; Matsopoulos, Anastassios; Mølholm, Martin; et al.
The paper outlines a cultural–psychological interpretation of the current European societies' socio-institutional crisis. To this end, preliminarily, the cultural psychological view of social behaviour is outlined, focusing on the idea that socio-political choices depend on how people make sense of their world. Second, the paper provides an interpretation of the current socio-political European scenario of crisis, based on the main results of a recent study that has mapped the cultural dynamics underpinning some European countries. The interpretation focuses on two complementary facets: on the one hand, the lack of symbolic resources (defined: semiotic capital) enabling people to perceive the collective dimension of life as a lived, subjectively relevant fact of experience; on the other hand, the relevance of a cultural form (defined: paranoid belongingness) that channels a trajectory of sensemaking consisting of the affective connotation of otherness in terms of threat and enemy. Third, the paper deepens the interplay between these cultural dynamics and the social, political and economic conditions that may have been triggered by them. In that perspective, the function of semiotic regulation played by the enemization of the other is highlighted. The conclusive part of the work is devoted to discuss implications the analysis suggests for policy makers.